Promoting sustainable urban neighborhood towards walkability / Diyanah Inani Azmi and Hafazah Abdul Karim. - Azmi, Diyanah Inani; Abdul Karim, Hafazah (Universiti Teknologi MARA Cawangan Selangor, 2018)
Climate change is a widely accepted fact. Urbanization and industrialization are the main cause of the climate change phenomena all around the world. One of the main problems of urbanization is the increase in growing dependence on automobiles. The main modes of transportation even in the neighborhood area are the private cars because it is the norm of urbanites to use the motorized vehicles rather than to walk. This shows that the planning and design of the neighborhood itself can influence the walkability of the housing area. This paper highlights the implication of walkability towards promoting sustainable urban neighborhood.